Full-band Monte Carlo simulation of thin InP p?i?n diodes - YOU, A; ONG, D (2005)
A full-band Monte Carlo (FBMC) model is developed to simulate the avalanche characteristics of thin InP p(+)-i-n(+) diode. The realistic energy band structure of InP used in this model is generated from the local empirical pseudopotential method. The electron and hole ionisation coefficients are fitted to the available measurement in the wide range of electric fields with a softer threshold than the Keldysh model. The multiplication gain and excess noise factor of electron-and hole-initiated multiplication in the thin InP p(+)-i-n(+) diodes were simulated using FBMC model. Our FBMC results are compared to a simple random path length (RPL) model. The FBMC model predicted lower noise as compare to the results simulated from RPL model in thin InP p(+)-i-n(+) diodes. (C) 2004 Elsevier Ltd. All rights reserved.